Crystal violet quantification of biofilm formation in MRSA wild-type, ΔyqhG, and complemented strains. - Jianhua Liao (1393228) (2025)
Crystal violet quantification of biofilm formation in MRSA wild-type, ΔyqhG, and complemented strains.